"Once again, a meth lab exploded and somebody died": Narratives of volatility and risk in the rural drug war. (December 2018) - Revier, Kevin
Methamphetamine ("meth") has received a massive amount of media attention in the United States over the last decade. In reporting, journalists, politicians, and police commonly link meth to widespread risk, violence, criminality, and rural decay. Although the rise in meth use, addiction, and crime has been largely overstated, such imagery legitimizes an expansion of surveillance and policing to rural landscapes. In this research, I examine the way meth and meth makers are represented in case coverage of a meth lab fire sited in upstate New York. I find that reporters narrate a more general meth lab "social problem formula story" with caricature villains (meth makers), victims (community members), and heroes (law enforcement and legislators). Significantly, this model of storytelling conveys a distorted and exaggerated understanding of meth as a social problem, turning the atypical meth lab case into the "typical, " while legitimizing law and order solutions. In contributing to the contemporary "methamphetamine imaginary, " this formula story forgoes a structural analysis that considers the prevailing global drug war, rural poverty, or broader capital inequality.